Inisialisasi Model Dampak Pembebanan Vertikal terhadap Pola Tumpukan Buah Tomat - Subarkah, Salim; Fitryanti, Rafika Indah; Arif, Saiful; Mutiara B, Ahmad Dony; Hiding Cahyono (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This study analyzes the potential damage to tomato fruits, which are susceptible to damage due to high water content and soft flesh. During the distribution process in Indonesia, shipments often utilize RPC crates without any protective layering, significantly increasing the risk of damage caused by friction and random vibration. The main objective is to analyze the impact of vibration through a static simulation on a 3D CAD model of a tomato fruit with applied loads of 5N, 10N, and 15N. The analysis specifically focused on the deformation and stress values experienced by the fruit under these conditions.The results indicated that the FCC 2 stacking pattern was the most effective in minimizing damage. This effectiveness is attributed to its compact arrangement and the greater number of contact points between fruits. Conversely, the Jumble 2 pattern exhibited the highest vulnerability. The Jumble 2 pattern recorded a maximum deformation of up to 6.3153mm and a maximum normal stress of 0.3410MPa (under a 15N load). The wider distribution of normal forces in the Jumble 2 pattern makes it more prone to damage. Therefore, a compact stacking pattern that maximizes contact points is crucial for reducing the percentage of tomato fruit damage during the shipping process.